Dietary Fiber Deficiency Accelerates Colitis in Mice in the Short Term Independent of Short-Chain Fatty Acids - Shoma Kanda; Haruki Usuda; Sonoko Karino; Takayuki Okamoto; Tomomi Niibayashi; Takahisa Yano; Kohji Naora; Koichiro Wada (Gastroenterology Insights)
It is believed that short-chain fatty acids (SCFAs)—the bacterial metabolites produced by the digestion of dietary fiber—potentially contribute to the prevention of colitis. However, this beneficial effect has not been conclusively proven. We thus attempted to verify this beneficial effect by examining whether colitis can be caused or worsened by the deficiency in dietary fiber in mice. We found that dextran sodium sulfate (DSS)-induced colitis was accelerated under a fiber-deficient condition, but the fiber deficiency itself did not provoke colitis. Moreover, episodes of diarrhea and epithelium damage in the large intestine were found upon analysis 24 h after the intervention. Unfortunately, these symptoms and tissue damage could not be ameliorated by administering SCFAs. On the other hand, a fiber-deficient condition increased the population of Desulfovibrio spp. and decreased the population of Lactobaccillus spp. regardless of the presence or absence of DSS upon analysis 24 h after the intervention. These results suggest that a deficiency in dietary fiber makes the intestinal environment irritable to colitis-inducing stimuli within the short term. This change does not appear to be related to the presence of SCFAs, but to the alteration of microbiota. Hence, a regular intake of dietary fiber is strongly recommended to avoid colitis and preserve intestinal health.